A Novel Optimizing Algorithm for DV based Positioning Methods in ad hoc Networks - Brida, P.; Machaj, J.; Duha, J. (Elektronika ir Elektrotechnika, 2010)
The optimizing algorithm for selection of reference nodes used in mobile positioning based on trilateration in wireless ad hoc networks is proposed in the paper. Position of reference nodes plays important role from positioning accuracy point of view. In case, that there is possibility to select some reference nodes from all it is useful do it. Therefore, there will be selected reference nodes which position is optimal in respect of localized blindfolded node. The properties and function of proposed algorithm are verified by means of simulation model of wireless ad hoc network. The following positioning methods DV-Hop, DV-Distance a DV-Euclidean are implemented into simulation model, because final position estimation of these methods is based on circular trilateration. More accurate results were achieved by implementation of proposed algorithm compare with the basic algorithms. Ill. 8, bibl. 10, tabl. 2 (in English; abstracts in English, Russian and Lithuanian).